Analysis of the Implementation of Patient Safety Targets by Nurses in Installations in Regional General Hospital dr. Fauziah Bireuen - Muzauwir Muzauwir; Arifah Devi Fitriani; Masnelly Lubis (Journal La Medihealtico, 2022)
Patient safety in a hospital is a service system in a hospital that provides safer patient care, including measuring risk, identifying and managing risks to patients, analyzing incidents, the ability to learn and follow up on incidents and implement solutions to reduce risks. This study aims to describe the implementation of patient safety goals by nurses on the quality of service in the inpatient room at RSUD dr. Fauziah Bireuen. This research is a qualitative research that will take place from November to December 2021. The research informants are the director of the hospital and 2 quality committee members at RSUD dr. Fauziah Bireuen, 7 nurses, 3 patients who are being hospitalized at RSUD dr. Fauziah Bireuen. The research instrument is interviews. The results of the research on the management of patient safety at the dr. General Hospital. Fauziah Bireuen has been implemented based on the Regulation of the Ministry of Health of the Republic of Indonesia in 2015 concerning the National Guidelines for Hospital Patient Safety and the Hospital Accreditation Commission. So that the results of this study can be used as input for making training programs for nurses related to patient safety.